Modelo de valoración con opciones reales, rejillas trinomial, volatilidad cambiante, sesgo y función isoelástica de utilidad; Valuation model with real options, trinomial lattice, changing volatility, bias and isoelastic utility functions - Gastón Milanesi (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– At emerging financial markets, the R&D, intangible and technological basis firms (TBF) valuation, they make the traditional real option binomial approach questionable. For that, a numerical model that modified the traditional binomial model is proposed, incorporating trinomial lattice, changing volatility, isoelastic utility function and variable risk aversion. These characteristics pretend improve the no conventional project valuation in emerging markets. It is employed the case method of analysis in administration, analysing the investment strategy valuation over a technological basis firm. The obtained results allow to compare the different values, from the classical binomial model until the proposed numerical model. The last showed superiority, because its incorporates explicitly variables in the valuation process, like the investor preference for risk and volatility levels according the life cycle.
Keywords: G13; G31; 330; real options; trinomial; changing volatility; isoelastic utility functions; variable risk aversion; start-up valuation